Dual Plating Fixation for Schatzker Type V And VI Tibial Plateau Fractures: A Prospective Analysis of 30 Cases Assessed with the Modified Rasmussen Criteria - Dr Rishabh Goyal; Dr Nishant Panegaon; Dr Mohammed Ibrahim, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Bicondylar (Schatzker V–VI) tibial plateau fractures pose a demanding reconstructive challenge because axial–varus/valgus forces destroy both columns and jeopardise soft tissues. Although dual plating has become popular, high quality prospective data from the Indian sub continent remain sparse. Methods: Between July 2022 and December 2023 we prospectively enrolled 30 consecutive adults (mean age 37.9 ± 9.4 years; 83 % men) with closed Schatzker V (n = 19) or VI (n = 11) fractures treated at a level I trauma centre. A standardised protocol was followed: anterolateral rafting 3.5/4.5 mm locking plate plus posteromedial antiglide/buttress plate through dual approaches, elevation of depressed segments, autograft or synthetic bone substitute as required, and early mobilisation. Functional and radiological outcomes were evaluated at 6 months with the Modified Rasmussen score; complications were recorded. Results: Mean surgical delay was 5.8 days (2–12). All fractures united (mean 19.7 weeks). The mean functional score was 27.4 ± 2.8; 15 (50 %) results were excellent, 13 (43 %) good and 2 (7 %) fair. Radiological scores paralleled clinical findings (excellent = 15, good = 9, fair = 4, poor = 2). Knee range of motion averaged 0–118°. Complications comprised knee stiffness (5 patients), medial column collapse (2), superficial infection (2) and one wound dehiscence; no non unions, neurovascular injuries or deep infections occurred. Conclusion: Anatomical dual column plating delivered reliable union, restoration of alignment and predominantly excellent to good functional results in complex bicondylar fractures, with an acceptable, mostly avoidable complication profile. Early soft tissue–respecting fixation, meticulous posteromedial buttressing and regimented rehabilitation appear pivotal.